Engaging postgraduates in a peer research group at the research proposal stage in a Malaysian university: support and challenges - Saeed, Murad Abdu; Ghazali, Kamila (Taylor & Francis, 2019)
Due to the increasing workloads for supervisors and the challenges in research proposals for postgraduates, the study focused on engaging 15 postgraduates in a Malaysian public university in a peer research group. The data was collected from observations of the group meetings, video-recorded peer feedback and follow-up interviews. The qualitative analysis of the data indicates that the research group supported the postgraduates through peer feedback practices, learning how to present proposals and defend themselves and finding directions in research proposals. Although their engagement was challenged by initial reservations of some postgraduates to present their proposals and provide feedback and issues related to provision, reception and reliability of peer feedback, these challenges were minimized through mentoring and instructional strategies. While peer research groups represent a valuable pedagogical support that complement supervisors’ support to postgraduates in developing their research proposals, the value should be maximized by integrating supervisors in research groups. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.